Chronic non-communicable diseases in Cameroon - burden, determinants and current policies - Echouffo-Tcheugui Justin B; Kengne Andre P (BMC, 2011)
Abstract Cameroon is experiencing an increase in the burden of chronic non-communicable diseases (NCDs), which accounted for 43% of all deaths in 2002. This article reviews the published literature to critically evaluate the evidence on the frequency, determinants and consequences of NCDs in Cameroon, and to identify research, intervention and policy gaps. The rising trends in NCDs have been documented for hypertension and diabetes, with a 2-5 and a 10-fold increase in their respective prevalence between 1994 and 2003. Magnitudes are much higher in urban settings, where increasing prevalence of overweight/obesity (by 54-82%) was observed over the same period. These changes largely result from the adoption of unfavorable eating habits, physical inactivity, and a probable increasing tobacco use. These behavioral changes are driven by the economic development and social mobility, which are part of the epidemiologic transition. There is still a dearth of information on chronic respiratory diseases and cancers, as well as on all NDCs and related risk factors in children and adolescents. More nationally representative data is needed to tract risk factors and consequences of NCDs. These conditions are increasingly been recognized as a priority, mainly through locally generated evidence. Thus, national-level prevention and control programs for chronic diseases (mainly diabetes and hypertension) have been established. However, the monitoring and evaluation of these programs is necessary. Budgetary allocations data by the ministry of health would be helpful, to evaluate the investment in NCDs prevention and control. Establishing more effective national-level tobacco control measures and food policies, as well as campaigns to promote healthy diets, physical activity and tobacco cessation would probably contribute to reducing the burden of NCDs.